The effects of region-level institutions and firm-level competences on firm’s innovativeness: evidence from the ICT industry in China - Hou, Fangfang (2020)
Innovation is a critical element for firms building competitiveness and for countries overcoming the limits to growth. Given the importance of innovation, existing literature has paid great attention to its determinants. Institutional theory suggests that the firm’s external institutional context plays an important role in the firm’s innovation performance. However, the current theory is mostly based on the assumption that institutions are homogeneous across regions within a given country. Recently, there is increasing evidence showing that institutions vary dramatically across regions within emerging economies. Still, the issues of how regional institutions can exert an influence on firms’ innovation have remained elusive and vague. Apart from the institutional context, another important focus of innovation literature is on firm-level attributes, drawing on the resource-based view (RBV). Institutional theory and the RBV have each in their own way contributed to the advancement of innovation literature, but each provides only a partial account. While the literature is replete with arguments that resources and institutions independently matter for firm behavior, it is still unclear whether the firm’s innovation benefits from its competences is dependent upon region-level institutions. Consistent with the recent calls for multilevel approaches to the study of the interplay between firm attribute and external environment, this study applies a multilevel research design to examine the determinants of the firm’s innovativeness. An integrative framework is developed focusing on the joint effects exercised by region-level institutions and firm-level competences on the firm’s innovativeness. Specifically, at region level, this study focuses on intellectual property (IP) protection, government intervention and market openness as three key aspects of regional institutions; and at firm level, it concerns technological competences and network competences as two key resources from both intra-firm and inter-firm dimensions. The model was validated using empirical evidence collected in the specific context of the Information and Communication Technology (ICT) industry in China. The sample used for data analysis consists of 462 listed ICT firms from 2008 to 2014. The results reveal that regional institutional idiosyncrasies in IP protection, government intervention and market openness do not serve as independent determinants of the firm’s innovativeness. Instead, they shape the firm’s innovativeness indirectly through the interplay with the firm’s technological and network competences. The results also suggest that the effects of region-level institutions and firm-level competences on firm innovativeness vary by innovation type. This study contributes to institutional theory by identifying the role played by institutions at region level in the firm’s innovativeness. Also, by combining the insights from the institutional theory and the RBV, this study identifies and contextualizes the relationship between the firm’s resources and its innovative behavior. It demonstrates how firms operating under different regional institutional contexts can fully unlock the potential of their resources to further enhance their innovativeness. Accordingly, suggestions can be offered to both policy makers and firms on how to enhance innovativeness.